The Factors that Affect Customer Ratings in E-Commerce Company - Yossi Naomi Magdalena; Teguh Raharjo; Dana Indra Sensuse (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2023)
In developing the e-commerce business in Indonesia, ecommerce companies must maintain customer satisfaction. In the e-commerce company, customer satisfaction can see from the ratings given by consumers. This research aims to find factors influencing consumers in providing ratings to improve services. The company’s current condition does not know the indicators when consumers give ratings. The current situation is decreasing order because the number of bad rating is higher and impact to profit company. This research uses several methods, such as the Unified Theory of Acceptance and Use of Technology (UTAUT), the Technology Acceptance Model (TAM), and product quality that influences ratings. The target respondents are consumers who have given bad ratings and have never been given a rating, with 326 respondents. The statistical analysis processing used was Partial Least Square (PLS) with SmartPLS v.4 tools. The results of the research concluded that the factors that influence bad rating respondents in giving ratings with significant positive results are the factors of perceived ease of use, social influence, and customer satisfaction, with an r-square rating value of 0.354 (moderate). From moderation, the variable with the most significant positive effect is the female gender. Meanwhile, respondents who have never been given a rating that has a significant positive impact are performance expectancy, social influence, and customer satisfaction, with an r-square value for ratings of 0.823 (strong). The results of this research concluded that there are several improvements to improve service, namely improving application algorithms, developing operational teams, and several strategies to overcome the impact of the covid pandemic.